RESULTS OF PRECLINICAL SAFETY TESTING COMPARISON FOR IBUPROFEN DRUG PRODUCTS - E. A. Sitnikova; S. G. Mardanly; E. P. Rogozhnikova (Разработка и регистрация лекарственных средств, 2019)
The article contains materials, methods and results of preclinical experimental test of acute toxicity of drugs «Ibuprofen», suspension for oral administration [for children], LP 001651 from 13.04.2012 and referent «Nurofen for children», suspension for oral administration, P N014745/01 from 22.08.2008. Ibuprofen preparations compared were found equivalent in acute toxicity studies. The work will be continued in order to prove the bioequivalence of the claimed preparations.